52.0k views
1 vote
Expand the expression (5x + 3)2, and write the result in standard form.

A.
25x2 + 9
B.
25x2 + 15x + 9
C.
25x2 + 24
D.
25x2 + 30x + 9

User Negash
by
5.8k points

2 Answers

1 vote

Answer:

option D is correct

The result in standard form is,


25x^2+30x+9

Explanation:

The standard form of the equation is given by:


y = Ax^2+Bx+C where, A, B and C are the coefficient and x is the variable.

Using the identity rule:


(a+b)^2 = a^2+2ab+b^2

Expand the expression:


(5x+3)^2

Apply the identity rule:


(5x)^2+2(5x)(3)+3^2


25x^2+30x+9

The result in standard form is,
25x^2+30x+9

Therefore, the result in standard form is,
25x^2+30x+9

User Joe Shakely
by
5.6k points
3 votes


(5x+3)^2\\\\\text{use}\ (a+b)^2=a^2+2ab+b^2\\\\=(5x)^2+2(5x)(3)+3^2\\\\=5^2x^2+30x+9\\\\=25x^2+30x+9\to D.

User Jnatalzia
by
6.2k points